Interaction Between Halotolerant Phosphate-Solubilizing Bacteria (Providencia rettgeri Strain TPM23) and Rock Phosphate Improves Soil Biochemical Properties and Peanut Growth in Saline Soil - Jiang, Huanhuan; Li, Sainan; Wang, Tong; Chi, Xiaoyuan; Qi, Peishi; Chen, Gang (Frontiers in Microbiology, 2021)
Soil salinity has adverse effects on soil microbial activity and nutrient cycles and therefore limits crop growth and yield. Amendments with halotolerant phosphate-solubilizing bacteria (PSB) and rock phosphate (RP) may improve properties of saline soil. In this study, we investigated the effects of RP either alone or in combination with PSB (Providencia rettgeri strain TPM23) on peanut growth and soil quality in a saline soil. With the combined application of RP and PSB, plant length and biomass (roots and shoots) and uptake of phosphorus (P), nitrogen (N), and potassium (K) increased significantly. Soil Na+ and Cl− contents decreased in the PR alone or PR combined with PSB treatment groups. There were strongly synergistic effects of RP and PSB on soil quality, including a decrease in pH of 0.62 units. In the combined RP and PSB treatment, soil available N content was 184.90 mg/kg; available P content was 39.00 mg/kg; and available K content was 524.99 mg/kg. In addition, phosphatase, urease, and dehydrogenase activities increased significantly, and the highest phosphatase activity was in the RP and PSB treatment (706.54 IU/L). The composition of rhizosphere soil bacterial communities was determined using 454-pyrosequencing of the 16S rRNA gene. In the PR alone or PR combined with PSB treatment groups, the structure of the soil bacterial community improved with increasing richness and diversity. With PSB inoculation, the relative abundance of Acidobacteria, Chloroflexi, and Planctomycetes increased. The three phyla were also positively correlated with soil available N and root dry weight. These results suggested microbiological mechanisms by which the combined use of RP and PSB improved saline soil and promoted plant growth. Overall, the study indicates the combined use of RP and PSB can be an economical and sustainable strategy to increase plant growth in P-deficient and salt-affected soils.